The Influence Of Financial Attitudes And Financial Capabilities In Improving Financial Welfare Through Digital Financial Literacy On Msme Actors - Hikma Ramadani; Goso; Duriani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of financial attitudes and financial abilities on financial welfare through digital financial literacy in MSME actors in Pancasila Field, Palopo City. Using a quantitative approach with a sample of 138 MSME actors, this study examined the direct and indirect relationships between variables using the PLS-SEM analysis technique. The results show that financial attitudes and financial ability have a significant positive influence on digital financial literacy, which in turn has a positive impact on financial well-being. A positive financial attitude can increase digital financial literacy, which then improves financial management and financial welfare of MSME actors. In addition, financial ability also plays an important role in facilitating the understanding of digital financial technology, which ultimately supports the improvement of financial well-being. This study suggests the importance of digital financial literacy education to empower MSME actors in managing their finances more efficiently and effectively.